A comparison of the effect of curcumin treatment on apoptosis, necrosis and autophagy in a MCF-7 mammary adenocarcinoma and a MCF-12A healthy mammary epithelial cell line - Van den Heever, Martine (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MSc (Physiological Sciences))--University of Stellenbosch, 2009.